OSMOLYTIC AND ADSORPTIVE ACTIVITIES DETERMINATION IN VITRO OF OINTMENT COMPONENTS ON THE BASIS OF CO2 EXTRACT FROM SEEDS OF SCHIZANDRA CHINENSIS - M. S. Makieva; Yu. A. Morozov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
There are data about positive effects from treatment of different skin diseases, sluggishly granulating wounds, and trophic ulcers with drugs based on Schizandra chinensis in literature sources. The purpose of this work is elaboration of soft external drug form - ointment on the basis of CO2 extract of Schizandra chinensis seeds. Biopharmaceutical researches in vitro were carried out to choose optimal ointment composition with osmolytic and absorptive activity. Researches on osmolytic activity determination were conducted by the common method of equilibrium dialysis through semi-permeable membrane; adsorption activity of model ointment compositions was registered on their capability to sorb coloring agent. Thus we have established that all model ointment compositions under consideration have osmolytic (by the efficiency as well as by duration) and adsorptive activity and can be used at different stages of wound process